A Luciferase-Expressing Leishmania braziliensis Line That Leads to Sustained Skin Lesions in BALB/c Mice and Allows Monitoring of Miltefosine Treatment Outcome. - Adriano C Coelho; Jordana C Oliveira; Caroline R Espada; Juliana Q Reimão; Cristiana T Trinconi; Silvia R B Uliana (Public Library of Science (PLoS), 2016)
Leishmania braziliensis is the most prevalent species isolated from patients displaying cutaneous and muco-cutaneous leishmaniasis in South America. However, there are difficulties for studying L. braziliensis pathogenesis or response to chemotherapy in vivo due to the natural resistance of most mouse strains to infection with these parasites. The aim of this work was to develop an experimental set up that could be used to assess drug efficacy against L. braziliensis. The model was tested using miltefosine.A L. braziliensis line, originally isolated from a cutaneous leishmaniasis patient, was passaged repeatedly in laboratory rodents and further genetically manipulated to express luciferase. Once collected from a culture of parasites freshly transformed from amastigotes, 106 wild type or luciferase-expressing stationary phase promastigotes were inoculated subcutaneously in young BALB/c mice or golden hamsters. In both groups, sustained cutaneous lesions developed at the site of inoculation, no spontaneous self- healing being observed 4 months post-inoculation, if left untreated. Compared to the wild type line features, no difference was noted for the luciferase-transgenic line. Infected animals were treated with 5 or 15 mg/kg/day miltefosine orally for 15 days. At the end of treatment, lesions had regressed and parasites were not detected. However, relapses were observed in animals treated with both doses of miltefosine.Here we described experimental settings for a late-healing model of cutaneous leishmaniasis upon inoculation of a luciferase-expressing L. braziliensis line that can be applied to drug development projects. These settings allowed the monitoring of the transient efficacy of a short-term miltefosine administration.